Material culture of multilingualism and affectivity - Aronin, Larissa (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
Affectivity is an important dimension in humans’ social and individual lives. It is either a stimulating or hindering aspect of language learning. This article aims to draw attention to material culture as a powerful, but mostly neglected source of data on the use and acquisition of languages, and demonstrates the close and intricate links between affectivity and material culture. It is hoped that revealing these interrelationships will assist in understanding and managing language diversity. It will allow practitioners and teachers to carry out social and private encounters, events and language teaching with more care, understanding and expertise. Researchers will be encouraged to join the investigation of yet one more important facet of multilingualism – material culture.
Keywords: material culture; multilingualism; affectivity; language use; language teaching